2020
DOI: 10.1149/1945-7111/abd2d8
|View full text |Cite
|
Sign up to set email alerts
|

Basal-Plane Orientation of Zn Electrodeposits Induced by Loss of Free Water in Concentrated Aqueous Solutions

Abstract: Concentrated aqueous solutions attract considerable attention because water electrolysis can be suppressed due to a decrease in the amount of free water. The present study focuses on electrodeposition behaviors of metallic zinc (Zn) using concentrated aqueous solutions containing bis(trifluoromethylsulfonyl)amide (Tf2N–) anions. An increase in Tf2N– concentration significantly enhances water-anion interactions, giving characteristic infrared spectra for the breakdown of the hydrogen-bonding networks of water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…No significant blueshift was observed in the Raman bands located at 745 cm −1 attributable to CF 3 bending vibration coupled with the S−N stretching mode of TFSA anions even with increasing NaTFSA concentration, meaning that the TFSA anions are not ligands for the Zn ions as well as Na ions, but rather are primarily coordinated by water molecules (Figure 1c). This is substantiated by the existence of the Raman bands between 380 to 425 cm −1 ascribed to [Zn(H 2 O) 6 ] 2+ [33] . In addition, the hydration are also supported by the results shown by Zhang et al .…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…No significant blueshift was observed in the Raman bands located at 745 cm −1 attributable to CF 3 bending vibration coupled with the S−N stretching mode of TFSA anions even with increasing NaTFSA concentration, meaning that the TFSA anions are not ligands for the Zn ions as well as Na ions, but rather are primarily coordinated by water molecules (Figure 1c). This is substantiated by the existence of the Raman bands between 380 to 425 cm −1 ascribed to [Zn(H 2 O) 6 ] 2+ [33] . In addition, the hydration are also supported by the results shown by Zhang et al .…”
Section: Resultssupporting
confidence: 72%
“…This is substantiated by the existence of the Raman bands between 380 to 425 cm À 1 ascribed to [Zn(H 2 O) 6 ] 2 + . [33] In addition, the hydration are also supported by the results shown by Zhang et al; they have found experimentally and computationally using X-ray total scattering, X-ray adsorption spectroscopy, and molecular dynamics simulation that Zn ions undergo six coordination by water molecules through oxygen atoms rather than TFSA anions in the water-in-salt electrolyte composed of 1 m Zn(TFSA) 2 and 20 m LiTFSA. [35] On the other hand, in the FT-IR spectra of the electrolytes with Cl-based salt, the increase in peak intensity attributable to the hydration of Zn ions was minor difference with increasing NaCl concentration from 1 to 6 m (Figure 1b).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Problems related to deposits morphologies are more pronounced in alkaline environment, where non-compact structures have a higher tendency to grow. This is one key reason for the increasing interest in alterative water-based electrolytes, among which mildly acidic (in battery chemistries such as zinc-ion battaries (ZIB), [24,25] rechargeable zinc-air batteries [26][27][28][29] and hybrid batteries with a Zn anode and a Li-ion intercalation cathode [16,17] ) and highly-concentrated [30,31] electrolytes: the focus of this work will be on the former approach. It is worth noting that the formation of mossy zinc occurs at lower c. d. s than compact deposits, so that the c. d. working range during charge which allows to have a high cyclability, has not only an upper limit due to dendritic growth but also a lower one, since Zn anodes might have problems also working at low c. d. s: it is worth stressing that the literature on Zn anodes did not address this issue, to date.…”
Section: Introductionmentioning
confidence: 99%